The ant generator - Harris, Elizabeth, 1944- (University of Iowa Press, 1991)
In the various interactions of mind and matter in Harris's affecting stories, people try to force their experience into simple shapes, against natural and social opposition, with comic or tragic results. Sometimes their determination to command their own meaning is redemptive and creative; at other times they confront the luminous mystery and unforgiving character of the natural world or the anger of the dispossessed. Harris sensitively creates individuals who respond to the ordinary in extraordinary ways, characters who think in dreams and visions and who, like the author, employ rare gifts.